Synthesis of multi-purpose fluoropolymer- and polyaniline-containing nanocomposites and their use in bioseparation, bioanalysis and diagnostics - D. V. Kapustin; V. P. Zubov (Тонкие химические технологии, 2011)
Traditional and improved methods of producing composite supports modified with nanolayers of fluoropolymers and polyanilines are reviewed. The methods provide the localization of the polymerization process at the surface layers of the carrier and additional functionality of the produced nanosystems. The effectiveness of the obtained materials in different fields of bioseparation and bioanalysis has been demonstrated